2018
DOI: 10.1371/journal.pone.0198188
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and effects on microbiota after in ovo administration of chicken cathelicidin-2

Abstract: Host Defense Peptides (HDPs) such as cathelicidins are multifunctional effectors of the innate immune system with both antimicrobial and pleiotropic immunomodulatory functions. Chicken cathelicidin-2 (CATH-2) has multiple immunomodulatory effects in vitro and the D-amino acid analog of this peptide has been shown to partially protect young chicks from a bacterial infection. However, the mechanisms responsible for CATH-2 mediated in vivo protection have not been investigated so far. In this study, D-CATH-2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Several studies have gone further to show that LL-37 has anti-cancer properties based on its ability to kill cancer cells in vitro (reviewed by Kuroda et al in [269]). LL-37 bioavailability in the colon, however, can affect gut microbiota viability and potentially perpetrate dysbiosis, as shown in chickens in the context of CATH-2 [270]. However, mice lacking the antimicrobial peptide CRAMP (CRAMP-KO) displayed oral dysbiosis following co-housing with wildtype mice, possibly transferred to the gut of the CRAMP-KO animals due to CRAMP presence in the feces of the latter [271].…”
Section: The Role Of the Microbiome In Regulating Nutrient Bioavailability And Immune Responsesmentioning
confidence: 99%
“…Several studies have gone further to show that LL-37 has anti-cancer properties based on its ability to kill cancer cells in vitro (reviewed by Kuroda et al in [269]). LL-37 bioavailability in the colon, however, can affect gut microbiota viability and potentially perpetrate dysbiosis, as shown in chickens in the context of CATH-2 [270]. However, mice lacking the antimicrobial peptide CRAMP (CRAMP-KO) displayed oral dysbiosis following co-housing with wildtype mice, possibly transferred to the gut of the CRAMP-KO animals due to CRAMP presence in the feces of the latter [271].…”
Section: The Role Of the Microbiome In Regulating Nutrient Bioavailability And Immune Responsesmentioning
confidence: 99%
“…As constituents of the neutrophil extracellular traps (Brinkmann, 2004) and nanonets in the intestine (Chu et al, 2012), HDPs can trap bacteria before intestinal translocation. HDPs can influence gut microbiota composition by influencing the expression of PRRs by intestinal epithelial cells (Tang et al, 2016;Cuperus et al, 2018). In addition to their effects on innate immunity, HDPs can boost adaptive immunity through the regulation of chemotaxis, maturation and activation of lymphocytes and DCs (Davidson et al, 2004).…”
Section: Hdpsmentioning
confidence: 99%
“…Therefore, knowledge of the development and variation of intestinal microbiota composition is pivotal for the design of strategies toward optimizing the intestinal health of broiler flocks. In poultry, it has been observed that the gut microbiota composition varies between flocks, flock cycles, breeds, and housing conditions and that many other unknown host and environmental factors exist (Cuperus, Kraaij, Zomer, van Dijk, & Haagsman, 2018; Johnson et al, 2018; Kers, Velkers, et al, 2019; Kers et al, 2018; Kim et al, 2015; Stanley, Geier, Hughes, Denman, & Moore, 2013).…”
Section: Introductionmentioning
confidence: 99%